"Maybe we should think outside the box?" prioritisation of issues with UK not-for-profit canine health and welfare research funding using Delphi expert consensus and gap analysis. - Alison M Skipper; Rowena M A Packer; Dan G O'Neill (PLoS ONE)
Over fifty participants, who together possessed broad research, veterinary and front-line expertise from across the canine health and welfare sector, contributed to a modified Delphi study to identify the highest priority research topics in UK canine health and welfare, the highest priorities for future research approaches, and the highest priorities for future reform in research processes and infrastructure, through group consensus. Further analysis also compared the prioritisation of selected research topics to the actual levels of research funding they previously received, through comparison with historical data. Most of the identified highest priority issues relating to canine health and welfare and its research concerned various aspects of the human-canine relationship, such as ownership or behavioural issues. Participants strongly emphasised the complexity of interrelated factors that impact the welfare of both dogs and people. Research topics identified as previously 'most underfunded' all concerned real-world canine welfare issues, particularly emphasising the breeding and supply of dogs. A supplementary analysis of historical research funding (2012-2022) for common chronic disorders in primary care practice, another identified highest priority topic, identified periodontal disease, anal sac disorders, overgrown nails and patellar luxation as the 'most underfunded' conditions. Most of the identified highest priority research approaches and methodologies concerned real-world design and execution aspects of canine health and welfare research, such as impact and engagement, with a strong focus on research investigating the human factors in canine welfare. Aspects of research funding infrastructure that were considered highest priority for future change mostly concerned increased transparency of funding processes and increased collaboration between stakeholder groups throughout the funding sector, which was strongly supported. Overall, these findings emphasise the importance of considering and including human factors and real-world impact, where appropriate, as key elements for optimising the relevance of canine health and welfare research.